Fast does not imply flawed: Analyzing emergency physician productivity and medical errors. Issue 6 (22nd November 2022) - Hoot, Nathan R.; Barbosa, Timothy J.; Chan, Hei Kit; Rogg, Jonathan G.
Abstract: Objective: To determine whether emergency physician productivity is associated with the risk of medical errors. Methods: We retrospectively analyzed quality assurance (QA) and billing data over 3 years at 2 urban emergency departments. Faculty physicians working 400 hours or more at either site were included. We measured physician years of experience, age, gender, patients seen per hour (PPH), and relative value units billed per hour (RVU/h). From an established QA process, we obtained adjudicated medical errors to calculate rates of medical errors per 1000 patients seen as the outcome. We discretized numeric variables and used Kruskal–Wallis testing to examine relationships between independent variables and rates of medical errors. Results: We included data for 39 physicians at site A and 42 at site B. The median rate of errors per 1000 patients was 1.6 (interquartile range [IQR], 1.1–1.9) at site A and 3.3 (IQR, 2.4–3.9) at site B. At site A, RVU/h was associated with error rates ( P = 0.03), with medians of 2.0, 1.2, 1.7, and 1.3 errors per 1000 patients, from slowest to fastest quartiles. At site B, PPH was associated with error rates ( P < 0.01), with medians of 3.9, 3.7, 2.4, and 2.7 errors per 1000 patients, from slowest to fastest quartiles. There was no significant relationship between error rates and PPH at site A or RVU/h at site B. Conclusions: Rates of medical errors were associated with 1 metric of physician productivity at each site, with higher error rates seen among physicians with slower productivity.